18 Evidence-based clinical quality indicators for occupational health services in the National Health Service (NHS). (11th October 2013) - Stilz, R R; Madan, I; Baker, A
Abstract : Objectives: The use of clinical quality indicators (QI) has been shown to raise standards and reduce variability in clinical care. Clinical QI can also be used for benchmarking and for commissioning services. Few occupational health QI are available. This project developed evidence-based QI for the spectrum of activities carried out by NHS occupational health services. Methods: A systematic literature search was performed, using a two-step hierarchical search strategy. Evidence-based national audits, national guidelines, Cochrane reviews, and systematic reviews were included. Evidence from the literature was translated into QI. Infeasible or irrelevant indicators and indicators based on low level evidence were excluded. Each indicator was assigned a score, reflecting its likely suitability for use in practice. Results: 151 evidence statements were extracted from 44 included publications, resulting in 131 QI. Excluding low grade evidence and irrelevant and infeasible indicators left 65 QI. From these the most suitable 18 QI were developed for activities relating to occupational health clinics, pre-commencement assessments, occupational health monitoring of organisations and occupational health interventions at an organisational level. Conclusions: These 18 QI will populate a new UK based occupational health data registry, the aim of which is to establish an evidence-based quality monitoring system for OHS in the NHS. However, many aspects are also applicable to services outside the NHS and outside the UK. Although these indicators were systematically developed and are based on best available evidence, further work needs to be done to validate theses QI in practice.